Pieces of the musical world : sounds and culture - Harris, Rachel; Pease, Rowan (Routledge, Taylor & Francis Group, 2015)
Pieces of the Musical World: Sounds and Cultures is a fieldwork-based ethnomusicology textbook that introduces a series of musical worlds each through a single "piece." It focuses on a musical sound or object that provides a springboard from which to tell a story about a particular geographic region, introducing key aspects of the cultures in which it is embedded, contexts of performance, the musicians who create or perform it, the journeys it has travelled, and its changing meanings.